2020
DOI: 10.1177/1756286420969501
|View full text |Cite
|
Sign up to set email alerts
|

The risk of polypharmacy, comorbidities and drug–drug interactions in women of childbearing age with multiple sclerosis

Abstract: Background and Aims: Multiple sclerosis (MS) is the most common neuroimmunological disease of the central nervous system in young adults. Despite recommended contraception, unplanned pregnancies can occur in women of childbearing age with MS. MS- and comorbidities-related multimedication in these patients represents a potential risk. We aimed to raise awareness regarding the frequency of polypharmacy and drug–drug interactions (DDIs) in female MS patients of childbearing age. Methods: Sociodemographic, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(90 reference statements)
0
14
0
Order By: Relevance
“… 33 , 40 We found in a smaller study of 131 women in childbearing age that the prevalence of having at least one pDDI of average danger was significantly higher in Pw/P than in Pw/oP (31.5% versus 5.2%, p < 0.001). 33 There were also significant associations between polypharmacy and higher age, higher degree of disability (EDSS score) and higher number of comorbidities. 33 In our recently published study, we found significantly higher pDDI prevalence rates for MS patients with cardiovascular, neurological, psychiatric and orthopaedic comorbidities.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“… 33 , 40 We found in a smaller study of 131 women in childbearing age that the prevalence of having at least one pDDI of average danger was significantly higher in Pw/P than in Pw/oP (31.5% versus 5.2%, p < 0.001). 33 There were also significant associations between polypharmacy and higher age, higher degree of disability (EDSS score) and higher number of comorbidities. 33 In our recently published study, we found significantly higher pDDI prevalence rates for MS patients with cardiovascular, neurological, psychiatric and orthopaedic comorbidities.…”
Section: Discussionmentioning
confidence: 75%
“… 33 There were also significant associations between polypharmacy and higher age, higher degree of disability (EDSS score) and higher number of comorbidities. 33 In our recently published study, we found significantly higher pDDI prevalence rates for MS patients with cardiovascular, neurological, psychiatric and orthopaedic comorbidities. 40 The present study focused on the analysis of pDDIs and their severity by incorporating information from Drugs.com .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…To our knowledge, there were no previous large-scale studies that addressed the issue of pDDIs in patients with MS until today. We previously evaluated pDDIs in MS patients, but this study was focused on a rather small group of women at childbearing age [ 31 ]. Comparisons to other chronic neurological or autoimmune diseases are difficult because the majority of studies dealing with pDDIs and PP were conducted in cohorts of elderly patients or nursing home residents [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%